2007
DOI: 10.1038/nature05635
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the yeast polarity protein Sro7 reveals a SNARE regulatory mechanism

Abstract: Polarized exocytosis requires coordination between the actin cytoskeleton and the exocytic machinery responsible for fusion of secretory vesicles at specific sites on the plasma membrane. Fusion requires formation of a complex between a vesicle-bound R-SNARE and plasma membrane Qa, Qb and Qc SNARE proteins. Proteins in the lethal giant larvae protein family, including lethal giant larvae and tomosyn in metazoans and Sro7 in yeast, interact with Q-SNAREs and are emerging as key regulators of polarized exocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
116
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 27 publications
8
116
0
Order By: Relevance
“…Sro7 and Sro77 interact with the exocyst and Sec4-GTP, as well as the t-SNARE Sec9 [58][59][60]. A new structure study suggests that Sro7 allosterically regulates the formation of the SNARE complex through its interaction with Sec9 [61].…”
Section: Exocytosismentioning
confidence: 99%
“…Sro7 and Sro77 interact with the exocyst and Sec4-GTP, as well as the t-SNARE Sec9 [58][59][60]. A new structure study suggests that Sro7 allosterically regulates the formation of the SNARE complex through its interaction with Sec9 [61].…”
Section: Exocytosismentioning
confidence: 99%
“…Structural analysis has shown that Sro7 is composed of two interlocking ␤-propellers with a long C-terminal tail that binds back to the N-terminal propeller in an autoinhibitory mode. The region bound by the tail was shown to overlap with the binding site of the plasma membrane t-SNARE Sec9 in a way that suggested the possibility of a "triggered" release of the SNARE by Sro7 (5). Although the Sec4 GTPase remained an attractive candidate triggering factor, its association with Sro7 had previously been shown to have no effect on Sro7's association with Sec9 (2).…”
mentioning
confidence: 98%
“…5A). The autoinhibitory tail is thought to regulate interaction of Sro7 with the Qbc-SNARE domain of the plasma membrane t-SNARE, Sec9 (5). To test the idea that the effect of the Asp-189 and Asp-222 mutations on clustering is through loss of the autoinhibitory interaction of the C-terminal domain with the propeller, we generated an additional set of mutations (N914K and S942F) in the C-terminal tail, which form strong hydrogen bond interactions with the two arginine residues on the N-terminal propeller (Fig.…”
Section: Novel Mutant Sro7-r189dr222d Fails To Cluster Postgolgi Vmentioning
confidence: 99%
“…Another downstream effector of Sec4 is Sro7, the yeast homolog of lethal giant larvae (lgl), implicated in epithelial polarity (Grosshans et al 2006;see Prehoda 2009). Sro7 was shown to bind to the t-SNARE protein Sec9 and is implicated in SNARE assembly (Lehman et al 1999;Hattendorf et al 2007). Sro7 also directly interacts with the exocyst component Exo84; disruption of the Sro7-Exo84 binding in cells lead to intracellular accumulation of secretory vesicles and defects in cell morphogenesis (Zhang et al 2005b).…”
Section: The Rab Family Of Small Gtp-binding Proteinsmentioning
confidence: 99%